Effect of Anti-Rheumatic Drugs on Cardiovascular Disease Events in Rheumatoid Arthritis - Baoqi, Yang; Dan, Ma; Xingxing, Zhao; Xueqing, Zhu; Yajing, Wang; Ke, Xu; Liyun, Zhang (Frontiers in Cardiovascular Medicine, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by erosive arthritis, which can involve multiple systems. Patients with RA may have a variety of comorbidities, including cardiovascular disease (CVD), lung cancer, lymphoma, infection, osteoporosis, fatigue, depression, colon cancer, breast cancer, prostate cancer, and Alzheimer's disease. Among these comorbidities, the incidence of CVD, lung cancer, lymphoma, infection, and osteoporosis is higher. CVD is a serious complication of RA. The risk of CVD and associated mortality rate in patients with RA is high, and the treatment rate is low. In addition to traditional risk factors, such as age, sex, blood pressure, and diabetes, RA is also associated with inflammation. Furthermore, therapeutic drugs for RA, including non-steroidal anti-inflammatory drugs, glucocorticoids, and disease-modifying anti-rheumatic drugs, have beneficial or harmful effects on cardiovascular events in patients with RA. This article discusses the effects of therapeutic drugs for RA on cardiovascular events.